The Effect of Work Motivation Performace of Elementary School Teachers - Purba, Lailatul Adila; Rambe, Hasian; Siregar, Siti Masdelina; Siregar, Meli Suryani; Naibaho, Dina; Lukmaw, Lukmaw (Edumaspul: Jurnal Pendidikan, 2022)
This research is used the effect of work motivation performance of elementary school teachers in the fulfillment of competitive human resources in the development of science and technology as well as substantial aspects, namely spiritual in order to be able to produce quality products. To avoid the rampant degradation of character, it is necessary to implement character education management in educational institutions. The purpose of this study was to determine the implementation of character education management through the principal’s academic supervision on the performance of elementary school teachers. This research uses qualitative methods. Qualitative research is research that presents data with a description. Data collection techniques are carried out by observation methods. This type of research is field research. Data analysis consists of three components, namely data reduction, data presentation and drawing conclusions. Based on the results of research, the implementation of character education management is integrated in school activities, namely the principal’s academic supervision on the performance of elementary school teachers. Character education management activities are carried out in order to achieve the vision and mission of the school. So, teacher work motivation is an encouragement that excites the teacher’s personality to play an active role in achieving learning goals. The encouragement comes from other people or comes from oneself. The process of the emergence of teacher work motivation is a combination of the components of needs, encouragement, goals and rewards